Technical Assistance Evaluation Program : Findings of Evaluations and Updated Program. (Policy Papers; Policy Paper ;, 2008)
CARTAC, the second of the regional technical assistance centers, was created with singular emphasis on ownership of technical assistance by the beneficiary countries. To this end, it was structured as a UNDP project with the IMF as Executing Agency and with a Steering Committee empowered to give strategic guidance to the program and select its senior staff from short lists provided by the IMF. With the spread of the RTAC modality, the IMF has sought to bring the Centers' activities within the ambit of overall resource planning for technical assistance, ensure consistency with the institution's view on priorities for technical assistance in the countries concerned, and tighten quality control through backstopping. This has created the potential for conflict with the relative independence that CARTAC has enjoyed from its inception. The conclusion in this report, however, is that alignment with the IMF does not necessarily undermine country ownership and that the Steering Committee can play a pivotal role in defusing any tension that may arise.